A Bilateral Zero-Voltage Switching Bidirectional DC-DC Converter with Low Switching Noise - Chien-Chun Huang; Tsung-Lin Tsai; Yao-Ching Hsieh; Huang-Jen Chiu (Energies, 2018)
This paper proposes a novel bilateral zero-voltage switching (ZVS) bidirectional converter with synchronous rectification. By controlling the direction and timing of excessive current injection, the main power switches can achieve bilateral ZVS under various loads and output voltages. Compared with the common soft-switching power converter with only zero-voltage turn-on, the proposed bilateral ZVS bidirectional converter can achieve both zero-voltage switching on and off in every switching cycle. This feature can alleviate the output switching noise due to the controlled rising and falling slope of the switch voltage. Furthermore, the voltage slopes almost remain unchanged over a wide range of output voltages and load levels. The most important feature of bilateral ZVS is to reduce the output switching noise. Experimental results based on a 1 kW prototype are presented to demonstrate the performance of the proposed converter. From experimental results on the proposed scheme, the switching noise reduction is about 75%.